Women's struggle for identity in Anita Desai's Clear Light of Day - Heidari, Marjan; Abbasiyannejad, Mina; Shobeiri, Ashkan (Common Ground Publishing, 2011)
In her novel Clear Light of Day, Anita Desai portrays Indian women as marginalized characters facing challenges and burdens imposed by patriarchal society. They resemble colonial subjects whose lives are fractured. Among the female characters Bim, Tara, their mother and Aunt Mira, all are subordinated by a male-dominant culture which underestimates female subjectivity. This paper illustrates how these women manage their precarious situation and stand up to a society controlled by men. This study reflects on these women’s lives to see how they find different ways to assert their existence. One way in which these female characters survive is by entering male dominated society and adopting their language and culture. As these women are unable to improve their circumstances, they struggle to establish their own identity using the oppressor’s language and culture.